Forecasting Handbook - Strannefors, Tord (Stockholm, 2004)
"The eighth report is a Forecasting Handbook written by the Swedish expert Tord Strannefors, Swedish National Labour Market Board, as part of the WLE’s labour market project in Bulgaria on regional implementation of labour market policies. Swedish forecasting methodology has developed gradually since its beginnings in the 1960s. The methodology has changed over time, with the current model introduced early in the 1990s. However, the Public Employment Offices have played a key role since the outset and information gathering has always been part of the Public Employment Offices’ natural interface with the business world. For short periods, the Public Employment Offices’ role was toned down, but this proved ineffective as the role of the forecast as a tool for operational and work planning was less successful during these periods."